2012
DOI: 10.1002/fsn3.11
|View full text |Cite
|
Sign up to set email alerts
|

β‐Glucan supplementation, allergy symptoms, and quality of life in self‐described ragweed allergy sufferers

Abstract: This randomized, placebo-controlled, double-blind study compared the effects of daily supplementation for 4 week with 250 mg Wellmune WGP® β-1,3/1,6-Glucan (WGP) with placebo 250 mg/day (rice flour) on physical and psychological health attributes of self-described “moderate” ragweed allergy sufferers. Study participants (mean age = 36 ± 9 year; range 18–53 year) were recruited before the beginning of ragweed season (September) in Northeastern Ohio. Serum IgE concentration, allergy symptoms [via self-report, Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 94 publications
2
22
0
2
Order By: Relevance
“…These results are consistent with studies linking protection against AM with LCPUFAs [ 12 , 34 ], prebiotics [ 21 , 22 , 35 ] and β-glucan [ 28 , 36 , 37 ]. Dietary LCPUFAs were associated with less atopic dermatitis and wheezing [ 12 , 34 ], and amelioration of symptoms in asthmatic children [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with studies linking protection against AM with LCPUFAs [ 12 , 34 ], prebiotics [ 21 , 22 , 35 ] and β-glucan [ 28 , 36 , 37 ]. Dietary LCPUFAs were associated with less atopic dermatitis and wheezing [ 12 , 34 ], and amelioration of symptoms in asthmatic children [ 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, prebiotic oligosaccharides support the immune system through stimulation of beneficial gut bacteria [ 17 20 ] and were associated with decreased respiratory infections and allergic diseases [ 21 24 ]. β-glucan, a polysaccharide derived from yeasts, fungi or bacteria, has also demonstrated immune-supporting properties [ 25 , 26 ], with data showing protection against respiratory infections and allergy in adults and children [ 26 28 ]. In a recent randomized clinical trial in 3- to 4-year-old children attending daycare in China, we demonstrated that daily consumption of a cow’s-milk based beverage (CMBB) containing a combination of nutrients including docosahexaenoic acid (DHA), the prebiotics polydextrose (PDX) and galactooligosaccharides (GOS), and yeast β-glucan, and enriched with micronutrients such as vitamin A, zinc and iron, was associated with fewer acute respiratory infections (ARI) compared to cow’s milk [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…En otro estudio se observó que la suplementación con 250 mg/día de WGP durante 4 semanas redujo significativamente en 28% los síntomas generales de alergia al polen de ambrosia y en 52% su intensidad; sin embargo, no tuvo ningún efecto en los niveles séricos de IgE. Por otra parte, la suplementación con WGP mejoró en 19% el estado físico general de los sujetos y en un 7% su bienestar emocional, en comparación con el grupo control (57). La actividad anti-alérgica de los β-glucanos también ha sido evaluada en estudios clínicos epidemiológicos y en estudios in vitro (58).…”
unclassified
“…Moreover, positive effects of immunomodulation by food have already been described in humans [4]. Specifically, Talbott [5] and Yamada [6] documented positive effects of supplementation of β-glucans on symptoms of pollen allergy. Results of the above studies demonstrate the antiallergic and anti-inflammatory properties of fungal immunomodulators and give hope for the future that they could be increasingly used in the treatment and prevention of atopy in larger populations.…”
Section: Immunomodulation In Atopic Diseasementioning
confidence: 96%